Pilot study of the efficacy of treatment of urticaria by using two traditional Vietnamese herbs administered systemically - Bach Thị Như Quỳnh; Pham Van Thức; Ninh Thị Kim Thu; Nguyen Thị Hien; Floch Katell; Nguyen Thị Hồng Liên; Carre Jean-Luc (International Journal of Dermatology and Clinical Research - Peertechz Publications, 2022)
Among the many plants used in traditional medicine in many countries, Averrhoa carambola L. and lonicera japonica Thunb are regularly the subjects of publications describing the pharmacological effects of their extracts.